Produção de amilases pelo cultivo em estado sólido de Rhizopus microsporus var. oligosporus e sua utilização na obtenção de xarope de glicose - Escaramboni, Bruna [UNESP] (2014)
The amylases belong to the class of the hydrolases and they are enzymes of great importance to industrial applications, representing from 25% to 33% of the worldwide enzymes business. There is a wide range of applications and a huge interest in the discovery of enzymes with better properties in the starch degradation. The present work aims to optimize the technology of production of amylases by Rhizopus microsporus var. oligosporus in solid state fermentation with wheat bran. In second stage the enzymatic extract was partially characterized and used in glucose syrup production. The ideal concentration of salts to supplement the culture medium was determined, as well as the influence of moisture and inoculum on amylase production using a central composite rotational design (DCCR). The best protocol for enzymatic extraction and profiles of amylase production at different temperatures of fermentation were determined. The enzymatic activity was measured by the quantification of reducing sugars released during hydrolysis reaction of starch. The lowest optimal concentration was 1.25% (w/w) ammonium sulfate, 0.25% potassium phosphate and 1.25% urea. The best moisture level for amylolytic production was 50%, and the most efficient extraction was with 10 ml of distilled water per gram of substrate. The maximum enzyme production in the cultures was at 30 °C for 120 h. The best temperature for amylolytic activity was 60 to 65 °C, and better stability (80%) was obtained up to 50 °C for 1 hour of incubation. The enzyme produced showed greater activity in a pH range 4.0-5.0, and more than 80% of stability after 1 hour of contact in a pH range 3.0-7.0. The crude enzymatic extract was able to perform the total conversion of starch to reducing sugar in 6 hours of reaction at 55 °C. For type II wheat flour was obtained a yield of 83% in 6.5 hours, and for wheat bran, 62% in 7 hours. The product of the catalytic reaction was concentrated to obtain 20% ...